Factors Influencing the Enhancement of Flexibility and Accountability in Financial Management Services under the BLUD Scheme at Community Health - Muhammad Ukas; Izaak Zoelkarnain Akbar; Bahrul Ilmi; Ahmad Yunani; Neka Erlyani (Newinera Publisher, 2026)
Transparent healthcare services has driven Community Health Centers (Puskesmas) to adopt the Financial Management Pattern of Regional Public Service Agencies (PPK-BLUD). This study aims to examine the factors influencing the flexibility and accountability of BLUD-based financial management within Community Health Centers in Kotabaru Regency. The research employs a literature review approach, utilizing content analysis of scholarly articles and relevant regulatory documents published within the last five years. The findings reveal that the effectiveness of BLUD implementation is predominantly shaped by four key determinants: the quality of human resources, regulatory frameworks, infrastructural capacity, and the structure of authority and governance